The Influence of Human Resource Development and Supervision on Employee Performance with Workload as an Intervening Variable in the Department of Public Works and Binjai City Spatial Planning - Prawira Parinduri, Sukralmanto; Isa Indrawan, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to analyze the effect of human resource development and supervision on employee performance with workload as an intervening variable. This type of research is associative quantitative. The population of this study is 79 employees with the sample used is also 79 (saturated sample). Data collection is done by giving a questionnaire. The data source used is the primary data source. The research model used is Path analysis with the measuring tool Smart PLS version 3.3.3. The results of the study are that workload has a positive and significant effect on employee performance. Supervision has a positive and significant effect on workload. Supervision has a positive and significant effect on Employee Performance. HR development has a positive and significant effect on workload. HR development has a positive and insignificant effect on workload. Supervision has a significant and positive effect on Employee Performance through Workload. HR Development affects Employee Performance through Workload with insignificant positive value.